ANALISIS SISTEM PLTS ON-GRID DI TRANS STUDIO MALL CIBUBUR DENGAN KAPASITAS 1507 kWp DITINJAU DARI ASPEK EKONOMI TEKNIK - Benyamin Hernan Cresvo Hutasoit; Susilo, Susilo; Nempung, Judo Ignatius (Prodi Teknik Elektro FT UKI, 2024)
The photovoltaic (PV) system installed at Trans Studio Mall Cibubur operates as an on-grid system designed to lower electricity expenses. It boasts a total capacity of 1507 kWp and has the potential to produce approximately 1,502,240 kWh annually. Between January and March 2024, the system achieved an energy saving of 406,560 kWh, out of an annual usage of 5,626,400 kWp recorded from September to November 2023. This led to a reduction in electricity costs amounting to IDR 421,106,125 for the same timeframe. The economic assessment indicates an initial investment of IDR 12,272,187,620 for the PV system, with yearly operating and maintenance (O&M) costs of IDR 92,581,876. Financial calculations reveal a positive Net Present Value (NPV) of IDR 5,125,472,158 and a Discounted Payback Period (DPP) of approximately 13 years and 7 months. The Break-Even Point (BEP) is anticipated in the 8.6th year, confirming that the project is a sound investment. Post-breakeven, the revenue generated from the PV system will convert into net profit, affirming the system’s economic viability. Keywords : PLTS, On-Grid, engineering economics